Characteristics of Friedel pairs and diffraction contrast tomography with non‐perpendicular rotation axis. (18th June 2015) - Yi, Qiru; Li, Gang; Zhang, Jie; Luo, Sheng‐Nian; Fan, Duan; Gao, Zhenhua; Wang, Yanping; Gao, Guanfeng; Jiang, Shiping; Jiang, Xiaoming
<x xml:space="preserve">Abstract</x> The characteristics of Friedel pairs in diffraction contrast tomography (DCT) are studied in the condition that the rotation axis of the sample is not exactly perpendicular to the incident X‐ray direction. For the rotation axis approximately aligned along the vertical direction, the Friedel pairs close to the horizontal plane are insensitive to the non‐perpendicularity of the rotation axis, and can be used to refine the sample‐to‐detector distance and X‐ray energy, while the Friedel pairs close to the vertical direction are sensitive to the non‐perpendicularity of the rotation axis, and can be used to determine the rotation axis orientation. The correct matching proportion of Friedel pairs decreases with increasing non‐perpendicularity of the rotation axis. A method of data processing considering rotation axis misalignment is proposed, which significantly increases the correct matching and indexing proportions of the diffraction spots. A pure aluminium polycrystalline sample is investigated using DCT at beamline 4W1A of Beijing Synchrotron Radiation Facility. Based on the analysis of Friedel pairs, the sample‐to‐detector distance and X‐ray energy are refined to be 8.67 mm and 20.04 keV, respectively. The non‐perpendicular angle of the rotation axis is calculated to be 0.10°. With these refined geometric parameters, the matching proportion of the spatial position of diffraction spots is 90.62%. Three‐dimensional reconstruction of the sample with 13 grains is realised using the algebraic reconstruction technique. It is demonstrated that the precise correction of the orientation of the sample rotation axis is effective in DCT suffering from rotation axis misalignment, and the higher accuracy in determining the rotation axis is expected to improve the reconstruction precision of grains.